Shame and Guilt in Dostoevsky’s “Crime and Punishment” - Deborah A. Martinsen (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2018)
This article shows how Dostoevsky’s narration in Crime and Punishment not only creates the expectation of a guilt script while offering readers a shame scenario but also plunges readers into Raskolnikov’s head before distancing us from his thinking. Because Raskolnikov commits murder in Part One, readers expect a guilt script: crime, repentance, punishment, expiation. But Dostoevsky’s narrator offers us a shame scenario, which has no fixed script. Shame relates broadly to human identity; guilt relates more narrowly to human action. In Crime and Punishment, Dostoevsky explores how the pain of shame at one’s identity leads Raskolnikov to commit murder. At the end of Part Six, Raskolnikov finally confesses his crime – an important acknowledgement of guilt, but he does not yet signal repentance. Dostoevsky thus keeps readers off-balance for the novel’s duration – we expect, but do not get, a guilt script until the Epilogue’s final pages. Dostoevsky strengthens this strategy by keeping the guilt script alive among the novel’s characters. Because most characters view Raskolnikov as a moral agent, they expect him to feel concern for others and to act accordingly. But he doesn’t. Since readers share characters’ expectations, their puzzlement becomes ours. As characters “read” Raskolnikov – his face, his words, his actions – trying to understand what motivates his actions, readers do the same. The discrepancy between what we all expect and what we witness keeps us guessing. Not until Raskolnikov realizes and admits his need for others, as he does at the end of the Epilogue when he is thrown at Sonya’s feet, can he see himself as the moral agent that Dostoevsky’s narrator, readers, and characterobservers have been expecting all along. Love, the most powerful moral emotion of all, allows Raskolnikov to get past his shame, admit his guilt, and rejoin the human community.